2016
DOI: 10.1038/gim.2016.40
|View full text |Cite
|
Sign up to set email alerts
|

A standardized, evidence-based protocol to assess clinical actionability of genetic disorders associated with genomic variation

Abstract: PurposeGenome and exome sequencing can identify variants unrelated to the primary goal of sequencing. Detecting pathogenic variants associated with an increased risk of a medical disorder allows the possibility of clinical interventions to improve future health outcomes in patients and their at-risk relatives. The Clinical Genome Resource, or ClinGen, aims to assess clinical actionability of genes and associated disorders as part of a larger effort to build a central resource on the clinical relevance of genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 22 publications
0
91
0
Order By: Relevance
“…The SFWG acknowledged the inherent subjectivity and difficulty of rating any given intervention as it applies to an individual but voted unanimously in favor of adding this fifth criterion. This achieved consistency with efforts of the NIH-funded Clinical Genome Resource (ClinGen) 5 Actionability Working Group, 6 which had already applied these five criteria to assign actionability scores (called "Actionability Evidence-based Summaries") 7 to genes/conditions on the SF list.…”
Section: Methodsmentioning
confidence: 66%
“…The SFWG acknowledged the inherent subjectivity and difficulty of rating any given intervention as it applies to an individual but voted unanimously in favor of adding this fifth criterion. This achieved consistency with efforts of the NIH-funded Clinical Genome Resource (ClinGen) 5 Actionability Working Group, 6 which had already applied these five criteria to assign actionability scores (called "Actionability Evidence-based Summaries") 7 to genes/conditions on the SF list.…”
Section: Methodsmentioning
confidence: 66%
“…Our analytic pipeline allowed for the identification of reported pathogenic variants in more than 4600 disease-associated genes but concluded with a manual review of the supporting evidence of each identified variant, allowing for variant classification using current ACMG standards and inclusion of only those variants meeting a rigorous evidence base for pathogenicity(35). The list of genes and variants considered reportable will likely change as new gene-disease associations are identified, better estimates of penetrance from unbiased samples are generated, and implications for prognosis and therapy are defined(36, 37). Indeed, the PDE11A variant (p.Thr58ProfsX41) reported to one participant was reclassified from VUS:FP to VUS after the study period and thus no longer meets MedSeq Project reporting criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid changes in our understanding of genetic disease frustrates the use of gene-panel tests; when a new gene or mechanism for disease is reported in the literature, a patient with a negative genetic test requires repeat testing with a second genetic test to include the new information. It is not difficult to imagine a future where a single comprehensive genetic test is ordered, such as genome sequencing, and the patient’s report is updated annually with new findings as our understanding of genetic diseases evolves (53,54). …”
Section: Current Limitations and Future Methodsmentioning
confidence: 99%